2015
DOI: 10.1039/c5ta01664a
|View full text |Cite
|
Sign up to set email alerts
|

Lithium transport through lithium-ion battery cathode coatings

Abstract: The surface coating of cathodes using insulator films has proven to be a promising method for high-voltage 10 cathode stabilization in Li-ion batteries, but there is still substantial uncertainty about how these films function. More 11 specifically, there is limited knowledge of lithium solubility and transport through the films, which is important for coating 12 design and development. This study uses first-principles calculations based on Density Functional Theory to examine the 13 diffusivity of interstitia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
98
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 109 publications
8
98
0
Order By: Relevance
“…Electronic and Li-ion conductivity are the two other important factors in coating design as addressed in recent studies5960, both of which should be high enough to have an effective coating material that does not result in large interfacial impedance and improves the electrochemical performance of the battery. These properties, however, strongly depend on extrinsic factors such as the morphology, microstructure and synthesis conditions, and therefore are hard to model and show significant variations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronic and Li-ion conductivity are the two other important factors in coating design as addressed in recent studies5960, both of which should be high enough to have an effective coating material that does not result in large interfacial impedance and improves the electrochemical performance of the battery. These properties, however, strongly depend on extrinsic factors such as the morphology, microstructure and synthesis conditions, and therefore are hard to model and show significant variations.…”
Section: Discussionmentioning
confidence: 99%
“…These properties, however, strongly depend on extrinsic factors such as the morphology, microstructure and synthesis conditions, and therefore are hard to model and show significant variations. For example, Xu et al 60. showed that most of the common coating materials do not allow adequate Li ion transport in crystalline form whereas their amorphous counterparts often provide fast enough Li + diffusion that allows effective conformal coating morphologies5960.…”
Section: Discussionmentioning
confidence: 99%
“…Surface coating can do a great benefit on the surface structure of electrode material and change the property of solid-liquid interface [15][16][17]. Up to now, there have been a number of metal oxides and fluorides acting as feasible coating materials [18][19][20][21][22][23][24].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Moreover, interfaces inevitably occur for cathode particles at their surface, either with a solid electrolyte interphase (SEI) or frequently a protective coating layer, the latter of which is typically comprised of insulating metal oxides or fluorides [7][8][9][10][11][12][13][14][15] or sometimes an electrochemically active material (e.g., Li-Ni-PO 4 coating layer) 16 .…”
Section: Introductionmentioning
confidence: 99%